Intra-articular lignocaine as a means of analgesia during manual reduction of acute anterior shoulder dislocation - Kadel, Manoj; Thapa, Shrawan Kumar; Marasini, Rudra; Thapa, Sushil; Dhakal, Shankar; Shrestha, Robin (Journal of College of Medical Sciences-Nepal, 2016)
Background & Objectives: Acute anterior shoulder dislocation needs prompt reduction of the dislocation. The ideal reduction method should be simple, fast, effective and non- traumatic, with minimal pain, and should not cause further injury to the affected shoulder. Intra-articular local lignocaine injection is a means of achieving analgesia with less complication, and allowing prompt patient discharge of patient after reduction. The study was conducted with objective to evaluate the effectiveness of intra-articular lignocaine for reduction of acute anterior shoulder dislocation. Materials & Methods: Twenty- one cases of acute anterior shoulder dislocation were reduced using intra-articular local lignocaine injection as a method of analgesia by modified Hippocrates method. Results: The mean age was 44.71 years ± SD 20.14 while 11 cases were reduced with one to six hours of injury. Pain assessed through application of a visual analogue scale during the maneuver revealed scores ranging from two to eight with mean score of 4.29 ± SD 1.55. Conclusion: This method is not only safe and effective but also reduces hospital stay and has negligible adverse effects making it a popular choice for most orthopedists.